Air quality implications from oxidation of anthropogenic and biogenic precursors in the troposphere - Link, Michael F., author; Farmer, Delphine, advisor; Fisher, Ellen R., committee member; Neilson, James R., committee member; Jathar, Shantanu H., committee member; Ravishankara, Akkihebbal R., committee member (Colorado State University. Libraries, 2019)
Oxidation chemistry in the troposphere drives the formation of air pollutants, harmful to human health and the natural world. Emissions from both anthropogenic and biogenic sources control the ways in which air pollution is formed and thus understanding the chemistry of the oxidation of these emissions enhances our ability to predict how air quality evolves in the future. Experiments simulating tropospheric oxidation chemistry on anthropogenic point sources show that identifying unique chemical processes resulting in air pollution allow for a greater specificity in how to pursue strategies for pollution mitigation policy with regional and hemispheric implications. This thesis focuses on the implementation of advancements in instrumentation and experimental techniques to understand how tropospheric oxidation of anthropogenic and biogenic precursors can produce air pollution. First, we subject vehicle exhaust to simulated tropospheric oxidation and quantify the formation of particulate matter and a toxic gas, isocyanic acid. We estimate how important oxidation of vehicle emissions are for these atmospheric pollutants for the South Coast Air Basin of California and the Seoul Metropolitan Region. Second, we investigate the propensity for isoprene to produce formic and acetic acid in laboratory oxidation experiments. We find that isoprene is likely a major source of formic acid in biogenically-influenced environments, however the exact mechanisms for formation remain unclear. Lastly, we use chemical ionization mass spectrometer measurements to quantify the fraction of oxidized carbon allocated to gas-phase organic acids from isoprene oxidation in laboratory experiments. Through comparison with field measurements from a forest in Alabama to a forest in Colorado we determine high levels of isoprene in Alabama are responsible for high levels of organic acids compared to Colorado. We also observe that influences of anthropogenic NOₓ suppress the formation of gas-phase organic acids suggesting as NOₓ levels decrease throughout the US in the future organic acids produced from oxidation from isoprene are likely to increase.
Keywords: chemical ionization; non-targeted analysis; tropospheric oxidation; mass spectrometry; air pollution; organic acids